The Relationship of Knowledge on the Behaviour of Generative Diseases in the Elderly - Herlina Herlina (International Journal Labs, 2023)
Degenerative diseases are the leading cause of death globally. World Health Organization data shows that of the 57 million deaths that occur in the world, as many as 36 million or almost two thirds are caused by degenerative diseases. To determine the relationship between knowledge and degenerative disease prevention behavior in the elderly in Patok Hamlet, Marunsu Village, Samalantan District in 2022. The method used in this study is analytic observational with a cross-sectional study approach. The sampling technique in this study used total sampling, namely taking samples from the entire existing population, namely all elderly people with degenerative diseases in Patok Hamlet, Marunsu Village, Samalantan District. Data was collected using a questionnaire. The analysis technique uses the chi-square test. The results show that as many as 64.3% respondents has lack knowledge. Negative behavior was reported by 53.6% respondents. There was a significant relationship between respondents' knowledge and prevention of behavior (p<0.05). There is a relationship between respondents' knowledge and prevention behavior regarding degenerative diseases in the elderly in Patok Hamlet, Marunsu Village, Samalantan District.